2021
DOI: 10.1101/2021.08.10.455860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parent-of-origin effects propagate through networks to shape metabolic traits

Abstract: Parent-of-origin effects are unexpectedly common in complex traits, including metabolic and neurological diseases. Parent-of-origin effects can be modified by the environment, but the architecture of these gene-by-environmental effects on phenotypes remains to be unraveled. Previously, quantitative trait loci (QTL) showing context-specific parent-of-origin effects on metabolic traits were mapped in the F16 generation of an advanced intercross between LG/J and SM/J inbred mice. However, these QTL were not enric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
3
2
0
Order By: Relevance
“…8). These findings are consistent with previous studies, in which many ASE genes in humans were associated with the immune response 28 , while parent-of-origin effects were enriched on metabolic traits in mouse 29 . The allelic gene activation during embryogenesis of hybrid Ciona showed that 72% ASE genes were species-of-origin effects, the other 28% ASE genes were parent-of-origin effects.…”
Section: Resultssupporting
confidence: 93%
“…8). These findings are consistent with previous studies, in which many ASE genes in humans were associated with the immune response 28 , while parent-of-origin effects were enriched on metabolic traits in mouse 29 . The allelic gene activation during embryogenesis of hybrid Ciona showed that 72% ASE genes were species-of-origin effects, the other 28% ASE genes were parent-of-origin effects.…”
Section: Resultssupporting
confidence: 93%
“…Conversely, parent-of-origin dependent ASE genes (excluding the 171 snoRNA cluster in the PWS/AS domain) were not enriched in the 76 F 16 QTLs showing imprinting effects (p = 0.47, Figure 6B ). Tissue-specific ASE gene sets were also not enriched in the QTL sets for any metabolic trait category (p > 0.05, Supplemental Figure S16 ), supporting previous work that shows parental expression biases are often not the direct source of imprinting QTL effects (Macias-Velasco et al 2021).…”
Section: Resultssupporting
confidence: 79%
“…Tissue-specific ASE gene sets were also not enriched in the QTL sets for any metabolic trait category (p > 0.05, Supplemental Figure S16), supporting previous work that shows parental expression biases are often not the direct source of imprinting QTL effects (Macias-Velasco et al 2021).…”
Section: Ase Genes Are Enriched In Qtls For Metabolic and Anatomical ...supporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, it can be used to efficiently identify divergent gene expression regulated by cis variation. For example, by comparing expression originated from the two alleles in an interspecific F1 hybrid of Drosophila, genes subject to cis and trans regulation were identified, providing a genome-wide characterization of the regulatory landscape 13,14 . A special case of allele specific expression (ASE) is the parent-of-origin effect, where expression is biased towards a particular allele according to its paternal or maternal origin.…”
Section: Introductionmentioning
confidence: 99%